The Application of Islamic Architecture Concept in BTN Residential Paya Bedi Aceh Tamiang - Dafrina, Armelia; Safitri, Nurliana; Fidyati, Fidyati (Rumoh Journal of Architecture, 2024)
House is a shelter for human and it is used as a place of refuge from dangers and threats from outside and protection from rain and the heat of the sun. The phenomenon that occurs in the construction of residential houses often ignores the application of Islamic concepts. Many of the homeowners are careless in designing the spatial orientation of the house to be built. The purpose of this study is to examine the application of the Islamic architecture concept at residential complex in BTN Paya Bedi, Rantau District, Aceh Tamiang Regency. The research method used is descriptive qualitative method by examining 14 houses sample. From observation, it was found that the Paya Bedi BTN housing has not fully implemented the Islamic concept. Among 14 houses sample studied, only 5 houses samples which actually implemented the Islamic concept. These 5 are in accordance with the Islamic concept based on spatial patterns designed to apply the hijab (boundaries) concept, so that the privacy of the occupants of the house can be maintained properly. Likewise with the bathroom, the position of the toilet is designed so that it does not face/back to the Qibla. Then a clean and well-maintained house, as well as efforts to save energy are also recommended in Islam.